2006
DOI: 10.1111/j.1752-0606.2006.tb01623.x
|View full text |Cite
|
Sign up to set email alerts
|

Essential Components of Curricula for Preparing Therapists to Work Effectively With Lesbian, Gay, and Bisexual Clients: A Delphi Study

Abstract: The purpose of this study was to determine the knowledge, experiences, and values that therapists should possess to provide quality therapy services to lesbian, gay, and bisexual (LGB) persons and their families. Using the Delphi method, consensus from a panel of experts on LGB topics was obtained on the components that training curricula should ideally include to prepare therapists adequately to work with this population. Panelists provide suggestions for important therapist values and qualities, key theoreti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
91
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(101 citation statements)
references
References 26 publications
9
91
0
Order By: Relevance
“…Despite efforts to incorporate topics on sexual orientation into curricula, it continues to be met with resistance. Graduates of family therapy training programs have had little training or coursework on sexual orientation (Godfrey, Haddock, Fisher, & Lund, 2006). Research has shown that more than 75% of family therapy graduates have had less than 2 hours of training related to sexually marginalized populations (Malley & Tasker, 1999) and slightly more than 60% of family therapists reported having received no training on affirmative therapy practices and LGB identity development (Rock, Carlson, & McGeorge, 2010).…”
Section: Sexual Orientation Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite efforts to incorporate topics on sexual orientation into curricula, it continues to be met with resistance. Graduates of family therapy training programs have had little training or coursework on sexual orientation (Godfrey, Haddock, Fisher, & Lund, 2006). Research has shown that more than 75% of family therapy graduates have had less than 2 hours of training related to sexually marginalized populations (Malley & Tasker, 1999) and slightly more than 60% of family therapists reported having received no training on affirmative therapy practices and LGB identity development (Rock, Carlson, & McGeorge, 2010).…”
Section: Sexual Orientation Trainingmentioning
confidence: 99%
“…In order to foster a supervision environment that is sensitive to sexual orientation and welcoming of LGB and heterosexual supervisees to discuss issues related to sexual orientation in supervision, practical approaches have been identified. Briefly, these strategies for supervisors include taping and reviewing supervision sessions when sexual orientation is discussed (Long, 2002), balancing the significance of sexual orientation in supervision (Hitchings, 1999;Storm et al, 2001), using films and literature in supervision that incorporate LGB characters, using language that is sensitive to sexual orientation (Bruss et al, 1997;Long & Serovich, 2003), attending LGB workshops, and reading LGB journal publications (Godfrey et al, 2006).…”
Section: Sexual Orientation Trainingmentioning
confidence: 99%
“…For example, Clark and Serovich (1997) While the accrediting bodies of the major mental health professions have called for the infusion of LGB issues into their curricula (Long & Serovich, 2003), there is a paucity of research about how well graduate programs are integrating LGB issues into their training and supervision. The research that does exist raises question about the effectiveness of training programs to incorporate more LGB issues in their curricula (Allison et al, 1994;Bepko & Johnson, 2000;Buhrke, 1989;Carlson et al, 2012;Glenn & Russell, 1986; Graham et al, 1984;Mackelprang, Ray, & Hernandez-Peck, 1996;Morrow, 1996; Murphy, 1991;Murphy et al, 2002;Phillips & Fischer, 1998;Rock et al, 2010; Whittman, 1995).LGB SUPERVISEES' EXPERIENCES OF LGB-AFFIRMATIVE AND NON-AFFIRMATIVE SUPERVISION (Carlson et al, 2012;Charlés, et al, 2005;Godfrey, Haddock, Fisher, & Lund, 2006;Green, 1996; Hernandez & Rankin, 2008;Long & Serovich, 2003;Rock et al, 2010) have offered suggestions for how to integrate sexual minority information into training, but no comprehensive study has looked specifically at the degree to which this is occurring across theory, research, andLGB Other mental health disciplines, particularly psychology and social work, have better addressed the extent to which graduate training is preparing students for work with theLGB population (Charlés, et al, 2005;Rock et al, 2010). However, based on studies that assessed trainees' experiences with LGB issues and/or their attitudes about working with the LGB population, it appears that graduate training does not adequately prepare students to competently work with LGB individuals, couples, and families (Allison et al, 1994; Croteau, Bieschke, Phillips, & Lark, 1998).…”
mentioning
confidence: 99%
“…LGB SUPERVISEES' EXPERIENCES OF LGB-AFFIRMATIVE AND NON-AFFIRMATIVE SUPERVISION (Carlson et al, 2012;Charlés, et al, 2005;Godfrey, Haddock, Fisher, & Lund, 2006;Green, 1996; Hernandez & Rankin, 2008;Long & Serovich, 2003;Rock et al, 2010) have offered suggestions for how to integrate sexual minority information into training, but no comprehensive study has looked specifically at the degree to which this is occurring across theory, research, and…”
mentioning
confidence: 99%
See 1 more Smart Citation